The Editorials: Towards Integrated Biodesign-related and Translational Plat-forms to Determine Co-Development for Adaptation of Innovative BIotechno ogies and to Prognosticate the Future of the Healthcare and Life Science Bio-industry - Medvedeva, Veronika; Rose, Noel; Miller, Andrew David; Cheng, R. Holland; Blokh, Sofia; Tyukavin, Aleksandr; Zemskov, Vladimir; Kovalev, Mikhail; Andronova, Natalia; Kobrinskii, Boris; Grigorieva, Tatiana; Moiseyakh, Marina; et al. (British Journal of Healthcare and Medical Research, 2022)
.